Water friendly room temperature phosphorescence doped materials prepared via metal organic framework matrix transformation. (February 2023) - Ni, Ai-Yun; Zhang, Bo-Lun; Zhang, Pei-Pei; Zhang, Jian-Jun; Wang, Hui-Yu; Feng, Ke-Xin; Liu, Shuqin; Ni, Jun; Duan, Chunying
Abstract: Stimuli-responsive room temperature phosphorescence (RTP) materials have wide applications. However, it is still a challenge to achieve water-induced recovery afterglow materials, and materials can maintain afterglow after prolonged contact with water. Herein we show that a RTP-silent metal-organic framework (MOF), MOF-5, can immediately emit green RTP upon water stimulation. Detailed studies show water causes transformation of MOF-5 into another more tightly packed framework. Besides, strong hydrogen bond network is constructed by H2 O molecules trapped in the channels. Both factors limit the motion of the ligand and stabilize the triplet state, resulting in RTP. Such structural transformation can be further used as a new doping strategy to prepare a series of water-awakened RTP phosphor@MOF composites with RTP color ranging from green to orange-red and durations of 3–6 s. Remarkably, the RTP of the composites can maintain at least six weeks when being soaked in water. Water-induced information encryption based on the composites has been demonstrated. This work not only sheds new light on the developing of water-friendly MOF-based RTP materials, but also provides a new strategy for the preparation of doped afterglow materials. Graphical abstract: Image 1 Present here is a new strategy to prepare phosphor/matrix composites with tunable room temperature phosphorescence properties evoked by water through structural transformation of the MOF matrix. Highlights: Water-awakened recovery room temperature phosphorescence. A new strategy to prepare RTP phosphor/matrix composite. Excellent water-stable RTP performance.